2016
DOI: 10.1063/1.4959207
|View full text |Cite|
|
Sign up to set email alerts
|

Silver photo-diffusion and photo-induced macroscopic surface deformation of Ge33S67/Ag/Si substrate

Abstract: Ge-chalcogenide films show various photo-induced changes, and silver photo-diffusion is one of them which attracts lots of interest. In this paper, we report how silver and Ge-chalcogenide layers in Ge 33 S 67 /Ag/Si substrate stacks change under light exposure in the depth by measuring timeresolved neutron reflectivity. It was found from the measurement that Ag ions diffuse all over the matrix Ge 33 S 67 layer once Ag dissolves into the layer. We also found that the surface was macroscopically deformed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
(58 reference statements)
0
10
1
Order By: Relevance
“…This means that the Ag ions immediately diffuse all over the Ch host layer once they dissolve into the Ch host layer upon light exposure. This diffusion process is the same as that of the stoichiometric Ge 33 S 67 /Ag/Si substrate, 29 and is in contrast to the S-rich case of Ag/Ge 20 S 80 (Ref. 25) and Ag/Ge 25 S 75 .…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…This means that the Ag ions immediately diffuse all over the Ch host layer once they dissolve into the Ch host layer upon light exposure. This diffusion process is the same as that of the stoichiometric Ge 33 S 67 /Ag/Si substrate, 29 and is in contrast to the S-rich case of Ag/Ge 20 S 80 (Ref. 25) and Ag/Ge 25 S 75 .…”
Section: Resultsmentioning
confidence: 80%
“…Therefore, we expect that Ag can dissolve into the Ch host layer by 8.9% by more extended light exposure. In our previous study on the Ge 33 S 67 /Ag/Si substrate, 29 the saturated content of Ag was estimated to be 20% (Ag 0.20 Ge 0.27 S 0.53 ). Kawaguchi and Maruno 10 also demonstrated that the total amount of photodoped Ag for Ag/Ge 33 S 67 is about twice that of Ag/Ge 40 S 60 .…”
Section: Time-resolved Neutron Reflectivity-photodiffusion Kineticsmentioning
confidence: 95%
See 3 more Smart Citations